Development of Supply Chain Management Sustainability Index (SCMsi) - Roshima Said; Corina Joseph; Mariam Rahmat; Wan Nailah Abdullah; Leily Adja Radjeman; Chattrarat Hotrawaisaya; Chanicha Moryadee (International Journal of Supply Chain Management, 2020)
The reason for the Sustainable Development Goals (SDG) is to sustain the preservation of planet and prosperity of society. Thus, it is necessary for corporations to have a reliable, relevant and standardized sustainability supply chain management (SSCM) reporting practice. Companies’ proper disclosure of its supply chain management information will enable stakeholders to evaluate the firm’s supply chain management performance efficiently. Using content analysis, this study proposes a development of a comprehensive SSCM disclosure checklist i.e., Supply Chain Management Sustainability Index (SCMsi). SSCM is an all-inclusive view of supply chain processes, logistics and technologies that considers the environmental, social, economic and legal aspects of a supply chain's components. It will become a benchmark in the reporting of SSCM indicators, besides acting as monitoring mechanism to measure listed companies in advancing sustainable development agenda. This paper will be useful for organization in identifying ideal criteria of SCMsi that will contribute towards the best practices of supply chain management.